At-line nanofractionation with parallel mass spectrometry and bioactivity assessment for the rapid screening of thrombin and factor Xa inhibitors in snake venoms. (February 2016) - Mladic, Marija; Zietek, Barbara M.; Iyer, Janaki Krishnamoorthy; Hermarij, Philip; Niessen, Wilfried M.A.; Somsen, Govert W.; Kini, R. Manjunatha; Kool, Jeroen
Abstract: Snake venoms comprise complex mixtures of peptides and proteins causing modulation of diverse physiological functions upon envenomation of the prey organism. The components of snake venoms are studied as research tools and as potential drug candidates. However, the bioactivity determination with subsequent identification and purification of the bioactive compounds is a demanding and often laborious effort involving different analytical and pharmacological techniques. This study describes the development and optimization of an integrated analytical approach for activity profiling and identification of venom constituents targeting the cardiovascular system, thrombin and factor Xa enzymes in particular. The approach developed encompasses reversed-phase liquid chromatography (RPLC) analysis of a crude snake venom with parallel mass spectrometry (MS) and bioactivity analysis. The analytical and pharmacological part in this approach are linked using at-line nanofractionation. This implies that the bioactivity is assessed after high-resolution nanofractionation (6 s/well) onto high-density 384-well microtiter plates and subsequent freeze drying of the plates. The nanofractionation and bioassay conditions were optimized for maintaining LC resolution and achieving good bioassay sensitivity. The developed integrated analytical approach was successfully applied for the fast screening of snake venoms for compounds affecting thrombin and factor Xa activity. Parallel accurate MS measurements provided correlation of observed bioactivity to peptide/protein masses. This resulted in identification of a few interesting peptides with activity towards the drug target factor Xa from a screening campaign involving venoms of 39 snake species. Besides this, many positive protease activity peaks were observed in most venoms analysed. These protease fingerprint chromatograms were found to be similar for evolutionary closely related species and as such might serve as generic snake protease bioactivity fingerprints in biological studies on venoms. Highlights: Rapid screening of snake venoms for inhibitors of thrombin and factor Xa is reported. Bioactivity and MS analysis are performed in parallel using at-line nanofractionation. High-resolution fractionation allows for construction of the bioactivity chromatogram. Peak shape and retention time of the bioactive detected reveal its accurate mass.